2012
DOI: 10.1666/11-129r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Paleoecologic and Biostratigraphic Significance of Trace Fossils From Shallow- to Marginal-Marine Environments From the Middle Cambrian (Stage 5) of Jordan

Abstract: The Hanneh Member (Cambrian Stage 5) of the Burj Formation and the Umm Ishrin Formation of Jordan represent a transgressive-regressive succession that contains twenty-eight ichnotaxa, including vertical burrows (Arenicolitesisp.,Diplocraterionisp.,Gyrolithes polonicus,Rosseliaisp.,Skolithos linearis, escape trace fossils), horizontal simple burrows and trails (Archaeonassa fossulata,Gordia marina,Helminthoidichnites tenuis,Palaeophycus tubularis,Planolites beverleyensis,P. montanus), plug-shaped burrows (Berga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 86 publications
2
29
0
Order By: Relevance
“…Cruziana is best interpreted as related to combined locomotion and feeding strategy (pascichnia) (Seilacher, 2007). It is widely accepted that the main producers of Cruziana in the marine Paleozoic were trilobites or trilobitomorphs (Seilacher, 1970(Seilacher, , 1985(Seilacher, , 1992Hofmann et al, 2012). Cruziana ranges in age from early Cambrian to Holocene (Seilacher, 1970;Muñiz Guinea et al, 2015), and has been reported from a varied spectrum of paleoenvironments, ranging from typical shallow-water marine to freshwater settings (Bromley and Asgaard, 1979;Crimes, 1987).…”
Section: Systematic Paleontologymentioning
confidence: 99%
“…Cruziana is best interpreted as related to combined locomotion and feeding strategy (pascichnia) (Seilacher, 2007). It is widely accepted that the main producers of Cruziana in the marine Paleozoic were trilobites or trilobitomorphs (Seilacher, 1970(Seilacher, , 1985(Seilacher, , 1992Hofmann et al, 2012). Cruziana ranges in age from early Cambrian to Holocene (Seilacher, 1970;Muñiz Guinea et al, 2015), and has been reported from a varied spectrum of paleoenvironments, ranging from typical shallow-water marine to freshwater settings (Bromley and Asgaard, 1979;Crimes, 1987).…”
Section: Systematic Paleontologymentioning
confidence: 99%
“…Archaeonassa was described from lakes, deltas and shallow seas (Knaust 2007aSarkar et al 2009;Hofmann et al 2012;Mángano et al 2013).…”
Section: Archaeonassa Fossulatamentioning
confidence: 99%
“…It is common in the Upper Buntsandstein (Röt), Lower Muschelkalk (Knaust 2007a) Skolithos is a dwelling burrow (domichnion) of suspension-feeding annelids (polychaete), sipunculans, phoronids, crustaceans (Alpert 1974;Miller and Knox 1985;Gouramanis et al 2003;Bressan and Palma 2009;Desjardins et al 2010;Hofmann et al 2012;Knaust 2012;Baucon and Felletti 2013a). It is interpreted as fodinichnia or equilibrichnia of deposit feeders (Kim et al 2002, Davies et al 2009Loughlin and Hillier 2010).…”
Section: Rhizocorallium Jenensementioning
confidence: 99%
“…The ichnogenera Rusophycus, Diplichnites and Cruziana are also found preserved on the same surface however, no short range taxon is found in the assemblage (Fig. 9E) suggesting that the zones of T. pedum cross over in these strata and occur together with Rusophycus throughout the Cambrian (Jensen & Mens 2001, Hofmann et al 2012, Srivastava 2012a, Pandey et al 2014. The Agronomic Revolution (Seilacher & Pflüger 1994, Seilacher 1999 subsequently triggered another revolution in selection of the substrate changes by the benthic organisms (Mángano & Buatois 2017).…”
Section: Taphonomymentioning
confidence: 98%